Pengaruh Gaya Kepemimpinan dan Motivasi Kerja terhadap Kinerja Karyawan PT. PLN (Persero) Unit Layanan Pelanggan Kota Kupang - Angelina Fitriyani Banase; Rolland E. Fanggidae; Ria E. I. Nafie; Ni Putu Nursiani (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to determine and explain the influence of leadership style and work motivation on the performance of employees at PT PLN (Persero) customer service unit in kupang city, as well as to analyze and explain the simultaneous influence of leadership style and work motivation on employee performance. This research is an associative study using a quantitative approach. It focuses on the relationships between variables and tests the hypotheses that have been previously formulated. The sample consisted of 35 employees selected using the saturated sampling technique. Data collection techinques in the field included questionnaires, interviews, observation, and documentation. The data were analyzed using Multiple Linear Regression Analysis with the help of SPSS version 22. The result show that leadership style has a positive and significant effect on employee performance, and work motivation also has a positive and significant effect on employee performance. Simultaneously, leadership style and work motivation have a positive and significant influence on employee performance. Based on the Adjusted R Square value, it is indicated that leadership style and work motivation contribute 56,7% to employeeperformance, while the remaining 40,8% is influenced by other variables outside the scope of this study